Understanding the effects of an interdisciplinary approach to parental representation in child welfare. (September 2020) - Gerber, Lucas A.; Guggenheim, Martin; Pang, Yuk C.; Ross, Timothy; Mayevskaya, Yana; Jacobs, Susan; Pecora, Peter J.
Highlights: We studied NYC's interdisciplinary law office approach to parental representation. We interviewed nearly 60 NYC Family Court stakeholders. We identified 3 mechanisms through which the interdisciplinary law office operates. We provide recommendations to consider the viability of implementing NYC's model. Abstract: Prior research demonstrates that the interdisciplinary law office approach to parental representation in child welfare, used in the New York City Family Court, speeds up the time to permanency for children in foster care with no effect on child safety. Interrogating these findings further, this study utilizes a qualitative interview-based design to understand how the model works in practice to impact the outcomes of families' cases. We interviewed 42 practitioners in the New York City Family Court and 17 parents who had had a recent child protection case in the New York City Family Court. Practitioners included judges, court attorneys, attorneys who represent parents in these cases, attorneys who represent children in these cases, and attorneys for the child welfare agency. Based on our analysis of these interviews, we identify three elements critical to the success of the interdisciplinary law office case practice approach: [1] uniform high-quality representation, [2] interdisciplinary practice, and [3] paying attention to the client's well-being. These results shed light on why interdisciplinary law office parental representation effectively hastens reunification for children in foster care as compared to a solo practitioner attorney.